Strategic Group in Textile Industry: Case Study at PT. Sunson Textile Manufacture, Tbk - Sarah Sentika; Nurhasanah Nurhasanah; Popy Rufaidah (Journal of International Conference Proceedings (JICP), 2018)
This paper aims to discuss the identification of a strategic group model in the textile industry in Indonesia. Strategic Group is a group of companies that compete in an industry by applying the same strategies (Porter 1979). This study explores the strategic group that reflects a group of companies engaged in the textile industry in Indonesia that using similar competition strategies and approaches to maintain their market positions in an industry. The study identifies PT. Sunson Textile Manufacture, Tbk is one of the players in the textile industry in Indonesia. The company produced various textile products such as yarn and cotton woven fabrics. The research method used is a case study that aims to expose information on research objects accurately by delivering the content in a structured and accurate manner. This case study research method is also used to describe a strategy used by companies as a strategy to deal with competition in industrial groups. The results of the study show the market leader holds the highest product sales using similar strategies with its main competitors in industry through its various product variants. However, even having many product variants does not guarantee the sale of products produces the highest value. Keywords: Strategic group, SWOT analysis, case study, textile industry